2023
DOI: 10.3390/catal13071141
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Antiviral Properties of Thermally Sprayed Coatings against Human Coronavirus HCoV-229E

Abstract: For decades, novel viral strains of respiratory tract infections have caused human pandemics and initiated widespread illnesses. The recent coronavirus disease 2019 (COVID-19) outbreak caused by the SARS-CoV-2 virus has raised an urgent need to develop novel antiviral coatings as one of the potential solutions to mitigate the transmission of viral pathogens. Titanium dioxide is considered an excellent candidate for viral disinfection under light irradiation, with the potential to be activated under visible lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Analyzing the influence of one-day UV-B irradiation on layers and their antiviral properties, it should be mentioned that the Zn, ZnT2 and ZnT3 coatings showed moderate antiviral activity, confirming that UV-B irradiation activated the nanoparticles. It is worth mentioning that the longer UV-B irradiation (48 h) deteriorated the antiviral effectiveness of all analyzed coatings, clearly showing that UV-B irradiation should not exceed 24 h. Alebrahim et al [2] also analyzed antiviral coatings containing TiO 2 , Cu 2 O, TiO 2 -Cu 2 O and TiO 2 -Al 2 O 3 nanoparticles. They confirmed that TiO 2 -Cu 2 O and TiO 2 -Al 2 O 3 -based coatings had higher activity than coatings with TiO 2 and Cu 2 O.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Analyzing the influence of one-day UV-B irradiation on layers and their antiviral properties, it should be mentioned that the Zn, ZnT2 and ZnT3 coatings showed moderate antiviral activity, confirming that UV-B irradiation activated the nanoparticles. It is worth mentioning that the longer UV-B irradiation (48 h) deteriorated the antiviral effectiveness of all analyzed coatings, clearly showing that UV-B irradiation should not exceed 24 h. Alebrahim et al [2] also analyzed antiviral coatings containing TiO 2 , Cu 2 O, TiO 2 -Cu 2 O and TiO 2 -Al 2 O 3 nanoparticles. They confirmed that TiO 2 -Cu 2 O and TiO 2 -Al 2 O 3 -based coatings had higher activity than coatings with TiO 2 and Cu 2 O.…”
Section: Discussionmentioning
confidence: 99%
“…Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2) is an agent that causes coronavirus disease . Despite the available treatments against SARS-CoV-2 and vaccination, there are still about 767 million cases of daily worldwide infections, including over 6.9 million deaths, due to the COVID-19 pandemic [1,2]. Additionally, RNA viruses, which have a high mutation rate, like SARS-CoV-2, increase the risk of multiresistant variant development with more virulence characteristics [1].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations